Thermo-physical properties and microstructural behaviour of biochar-incorporated cementitious material. (1st April 2023) - Ali, Dilshad; Agarwal, Rachit; Hanifa, Mohd; Rawat, Pradeep; Paswan, Rakesh; Rai, Devendra; Tyagi, Inderjeet; Srinivasarao Naik, B.; Pippal, Ashish
Abstract: Biochar made from sawdust (1 wt%, 3 wt%, and 5 wt%) can be integrated into cementitious materials to reduce environmental pollutants and landfill waste. Biochar feedstocks were chosen from biomass wastes from the wood sector (sawdust) collected in Roorkee, Uttarakhand, India. The biochar was prepared using a slow pyrolysis method at 500 °C. FESEM, XRD, TGA, and isothermal calorimetry, were used to study the effects of biochar on hydration products. The water density, porosity, water absorption, and compressive strength of biochar were investigated after replacing it with cement paste. In addition, cement paste samples were tested for their thermal properties. It was found that biochar contributed to the improvement of cementitious compounds (hydration products). After 28 days, the compressive strength of the concrete was enhanced by replacing 1 wt%, 3 wt%, and 5 wt% with biochar due to enhanced pozzolanic reactions. Thermal conductivity, specific heat, and thermal diffusivity improved with increasing biochar dosage. In addition, water absorption decreased with increasing biochar doses in the cement matrix. As compared to the three different replacements, the 3 wt% replacement performed better than the 1 wt% and 3 wt% replacements. Graphical abstract: Image 1 Highlights: Biochar preparation in muffle furnaceat 500 °C under nitrogen and pressure condition. Biochar replaced cement with 1% 3% and 5 wt%. Determined physical, mechanical and thermal properties. Microstructural and mineral study of biochar replaced cement whereas examined hydration products after 28 days.